2015
DOI: 10.15432/jkto.2015.20.1.023
|View full text |Cite
|
Sign up to set email alerts
|

A case report of a clinically diagnosed advanced lung cancer patient after treatment with Gunchilgyebok-Jung

Abstract: Objective : This case report presents the effects of Gunchilgyebok-Jung to a patient who was clinically diagnosed with advanced lung cancer. Methods : The study involved a 74-year-old male patient clinically diagnosed with advanced (stage Ⅲ) lung cancer by chest computed tomography (CT) and positron emission tomography. The patient had two masses (11.32 mm and 23.03 mm × 35.34 mm) in the right upper lobe of the lung and in the mediastinum respectively. Gunchilgyebok-Jung commonly used for its anti-tumor and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research reported that Rhus verniciflua Stokes had therapeutic effects in patients with NSCLC, in that it prolonged survival time and was well tolerated [ 10 ]. Park et al [ 11 ] reported that geonchilgyebok- jeong treatment had considerable anti-tumor effect and immunopotentiating activity, without adverse effects, in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that Rhus verniciflua Stokes had therapeutic effects in patients with NSCLC, in that it prolonged survival time and was well tolerated [ 10 ]. Park et al [ 11 ] reported that geonchilgyebok- jeong treatment had considerable anti-tumor effect and immunopotentiating activity, without adverse effects, in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%